2021
DOI: 10.1016/j.jss.2021.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Increased Incidence of COVID-19 Infections Amongst Interpersonal Violence Patients

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Some of these studies included time periods encompassing the start of the pandemic itself (January 2020) [11 ▪▪ ,15 ▪ ,16 ▪ ], whereas others specifically examined time periods during which stay-at-home orders were in place in their respective states [4 ▪▪ ,10 ▪ ,12 ▪ ,13 ▪ ,17 ▪▪ ]. As such, it is difficult to make definitive conclusions on whether the observed decline in trauma volumes can be attributed to the virus itself or to the stay-at-home orders.…”
Section: Impact Of Coronavirus 2019 On Trauma Volumesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of these studies included time periods encompassing the start of the pandemic itself (January 2020) [11 ▪▪ ,15 ▪ ,16 ▪ ], whereas others specifically examined time periods during which stay-at-home orders were in place in their respective states [4 ▪▪ ,10 ▪ ,12 ▪ ,13 ▪ ,17 ▪▪ ]. As such, it is difficult to make definitive conclusions on whether the observed decline in trauma volumes can be attributed to the virus itself or to the stay-at-home orders.…”
Section: Impact Of Coronavirus 2019 On Trauma Volumesmentioning
confidence: 99%
“…Being injured as a result of interpersonal violence (e.g. blunt assault, SW, GSW) was an independent risk factor for a positive COVID-19 screen at the time of admission (OR 2.4) [4 ▪▪ ]. One proposed explanation was that interpersonal violence generally requires close physical contact, which may not be true of other trauma mechanisms such as MVCs.…”
Section: Impact Of Coronavirus 2019 On Mechanisms Of Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…These factors likely contributed to the significant rise in IPV-related injuries and emergency room visits during the pandemic 26 27. One study even found a higher incidence of COVID-19 in trauma patients with injuries due to IPV 28. While there are many ways in which COVID-19 compounded the struggles faced by IPV victims, it has also highlighted some of the greatest systemic barriers to providing resources for those experiencing or at risk for experiencing abuse.…”
Section: Introductionmentioning
confidence: 99%